2016
DOI: 10.3390/nu8120809
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Bovine Whey Protein Concentrate and Hydrolysate Preparation Methods on Motility in the Isolated Rat Distal Colon

Abstract: Whey protein concentrate (WPC) and hydrolysate (WPH) are protein ingredients used in sports, medical and pediatric formulations. Concentration and hydrolysis methods vary for whey sourced from cheese and casein co-products. The purpose of this research was to investigate the influence of whey processing methods on in vitro gastrointestinal (GI) health indicators for colonic motility, epithelial barrier integrity and immune modulation. WPCs from casein or cheese processing and WPH (11% or 19% degree of hydrolys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 25 publications
1
7
0
Order By: Relevance
“…DAI scores (DAI = weight loss percentage score + diarrhea score + rectal bleeding score) rely on weight loss and diarrhea which could be lowered by daily intake of BLG. Therefore, our hypothesis is that it also has some effect on bowel moment, appetite and intestinal mobility in the distal colon, which could be related to hardening of stool and less diarrhea, which is supported by literature. …”
Section: Resultssupporting
confidence: 75%
“…DAI scores (DAI = weight loss percentage score + diarrhea score + rectal bleeding score) rely on weight loss and diarrhea which could be lowered by daily intake of BLG. Therefore, our hypothesis is that it also has some effect on bowel moment, appetite and intestinal mobility in the distal colon, which could be related to hardening of stool and less diarrhea, which is supported by literature. …”
Section: Resultssupporting
confidence: 75%
“…[ 70 ] Concerning the whey fraction of milk, it has been found in the isolated rat distal colon assay that whey proteins concentrates decreased motility, while increased frequency of contractions was found for whey proteins hydrolyzates. [ 71 ] These authors hypothesized that differences between abundance of bioactive peptides in the dairy preparations might explain the opposite effects, as the maximum degree of protein hydrolysis was associated to the highest motility in the tissue. Likewise, hypothesis that whey proteins show faster gastrointestinal transit than casein, being this accentuated in the case of hydrolyzates, was further proved in vivo by using an aged rat model.…”
Section: Bioactivity Of Peptides Over Digestive Healthmentioning
confidence: 99%
“…In order to be successful C. rodentium needs to adhere to the GI tract where upon it adapts to the GI environment and undergoes a virulence switch to facilitate colonization of the distal colon and rectum ( Wiles et al, 2004 , 2006 ). In a recent study it was demonstrated that gut motility was reduced in rats fed WPC ( Dalziel et al, 2016 ). We suggest that this could, in part, explain the apparent success of C. rodentium in the WPC fed mice, where reduced gut motility may have favoured pathogen colonisation.…”
Section: Discussionmentioning
confidence: 99%